Answer:
See explanation
Step-by-step explanation:
Triangle ABC ha vertices at: A(-3,6), B(0,-4) and (2,6).
Let us apply 90 degrees clockwise about the origin twice to obtain 180 degrees clockwise rotation.
We apply the 90 degrees clockwise rotation rule.
![(x,y)\to (y,-x)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cto%20%28y%2C-x%29)
![\implies A(-3,6)\to (6,3)](https://tex.z-dn.net/?f=%5Cimplies%20A%28-3%2C6%29%5Cto%20%286%2C3%29)
![\implies B(0,4)\to (4,0)](https://tex.z-dn.net/?f=%5Cimplies%20B%280%2C4%29%5Cto%20%284%2C0%29)
![\implies C(2,6)\to (6,-2)](https://tex.z-dn.net/?f=%5Cimplies%20C%282%2C6%29%5Cto%20%286%2C-2%29)
We apply the 90 degrees clockwise rotation rule again on the resulting points:
![\implies (6,3)\to A''(3,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%286%2C3%29%5Cto%20A%27%27%283%2C-6%29)
![\implies (4,0)\to B''(0,-4)](https://tex.z-dn.net/?f=%5Cimplies%20%284%2C0%29%5Cto%20B%27%27%280%2C-4%29)
![\implies (6,-2)\to C''(-2,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%286%2C-2%29%5Cto%20C%27%27%28-2%2C-6%29)
Let us now apply 90 degrees counterclockwise rotation about the origin twice to obtain 180 degrees counterclockwise rotation.
We apply the 90 degrees counterclockwise rotation rule.
![(x,y)\to (-y,x)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cto%20%28-y%2Cx%29)
![\implies A(-3,6)\to (-6,-3)](https://tex.z-dn.net/?f=%5Cimplies%20A%28-3%2C6%29%5Cto%20%28-6%2C-3%29)
![\implies B(0,4)\to (-4,0)](https://tex.z-dn.net/?f=%5Cimplies%20B%280%2C4%29%5Cto%20%28-4%2C0%29)
![\implies C(2,6)\to (-6,2)](https://tex.z-dn.net/?f=%5Cimplies%20C%282%2C6%29%5Cto%20%28-6%2C2%29)
We apply the 90 degrees counterclockwise rotation rule again on the resulting points:
![\implies (-6,-3)\to A''(3,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%28-6%2C-3%29%5Cto%20A%27%27%283%2C-6%29)
![\implies (-4,0)\to B''(0,-4)](https://tex.z-dn.net/?f=%5Cimplies%20%28-4%2C0%29%5Cto%20B%27%27%280%2C-4%29)
![\implies (-6,2)\to C''(-2,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%28-6%2C2%29%5Cto%20C%27%27%28-2%2C-6%29)
We can see that A''(3,-6), B''(0,-4) and C''(-2,-6) is the same for both the 180 degrees clockwise and counterclockwise rotations.
right 3 units down 5 units
![f(x)=x^2](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2)
right 3 units = (3,0)
down 5 units = (0,-5)
vertex = (h,k) therefore.
![g(x)=(x-3)^2-5](https://tex.z-dn.net/?f=g%28x%29%3D%28x-3%29%5E2-5)
Then convert the vertex form into standard form for the equation in the choice.
![g(x)=(x-3)^2-5\\g(x)=(x^2-6x+9)-5+9\\g(x)=(x^2-6x)+4\\g(x)=x^2-6x+4](https://tex.z-dn.net/?f=g%28x%29%3D%28x-3%29%5E2-5%5C%5Cg%28x%29%3D%28x%5E2-6x%2B9%29-5%2B9%5C%5Cg%28x%29%3D%28x%5E2-6x%29%2B4%5C%5Cg%28x%29%3Dx%5E2-6x%2B4)
Thus, the answer is B.
Answer:
9x^4=6,561x
6x^2=36x
6561x+36x=6597x
Step-by-step explanation:
9x to the 4th power is just 9x9=81x9 and so on and the same goes for 6 then you just add them. Not Sure if this is the way you needed but feel free to ask anything.
Answer:
2.45
Step-by-step explanation:
The answer is the C let me know if you need the work